Skills Development and Training Interventions in Africa: Findings, Challenges, and Opportunities - Bernd Beber; Regina Dworschak; Tabea Lakemann; Jann Lay; Jan Priebe (RWI - Leibniz-Institut für Wirtschaftsforschung, 2021)
Skills trainings that target individuals or small businesses feature prominently in the development assistance landscape. They are an important vehicle for both bilateral and multilateral economic support. One estimate puts the volume of skills training interventions facilitated by the World Bank alone at about a billion U.S. dollars per year (Blattman and Ralston 2015). This briefing serves to summarize key insights that have so far been generated in the related research literature, identify study gaps that remain, discuss core challenges that compelling impact evaluations must grapple with, and outline one such set of evaluations that is planned to accompany Invest for Jobs. (...)
Additional information: Projektbericht für das Bundesministerium für wirtschaftliche Zusammenarbeit und Entwicklung
Keywords: 330